Functionalized Phenylbenzamides Inhibit Aquaporin-4 Reducing Cerebral Edema and Improving Outcome in Two Models of CNS Injury. (15th April 2019) - Farr, George W.; Hall, Christopher H.; Farr, Susan M.; Wade, Ramon; Detzel, Joshua M.; Adams, Amielia G.; Buch, Jasen M.; Beahm, Derek L.; Flask, Christopher A.; Xu, Kui; LaManna, Joseph C.; McGuirk, Paul R.; et al.
Abstract: Cerebral edema in ischemic stroke can lead to increased intracranial pressure, reduced cerebral blood flow and neuronal death. Unfortunately, current therapies for cerebral edema are either ineffective or highly invasive. During the development of cytotoxic and subsequent ionic cerebral edema water enters the brain by moving across an intact blood brain barrier and through aquaporin-4 (AQP4) at astrocyte endfeet. Using AQP4-expressing cells, we screened small molecule libraries for inhibitors that reduce AQP4-mediated water permeability. Additional functional assays were used to validate AQP4 inhibition and identified a promising structural series for medicinal chemistry. These efforts improved potency and revealed a compound we designated AER-270, N-[3, 5-bis (trifluoromethyl)phenyl]-5-chloro-2-hydroxybenzamide. AER-270 and a prodrug with enhanced solubility, AER-271 2-{[3, 5-Bis(trifluoromethyl) phenyl]carbamoyl}-4-chlorophenyl dihydrogen phosphate, improved neurological outcome and reduced swelling in two models of CNS injury complicated by cerebral edema: water intoxication and ischemic stroke modeled by middle cerebral artery occlusion. Highlights: High throughput screening of small molecule libraries reveals an inhibitor of Aquaporin-4. Medicinal chemistry leads to development of AER-270 and IV prodrug AER-271, selective partial antagonist of Aquaporin-4. Aquaporin-4 inhibitor AER-270 prevents cerebral edema and improves survival in a mouse model of water intoxication. Aquaporin-4 inhibitor AER-271 reduces cerebral edema and improves neurological outcomes in rodent ischemic stroke models.